Word 2000 in no time - Schwabe, Rainer-Walter (In no time, 2000)
Don't fumble your way round Word 2000 - it's much easier to go by the book Word 2000 in no time is the fast and easy way to learn the basics of Microsoft's powerful word processor. Every major task is laid out for you - step-by-step. You'll have Word 2000 unscrambled and running like clockwork in no time! It's Easy! With sample screens to illustrate every point, Excel 2000 is simplicity itself. Complete with a visual TOC: and jargon busting glossary, Word 2000 in no time is the fastest, easiest way to master your software. Learn how to: Get started Create all kinds of documents Enter, edit and manipulate text Build attractive presentations Use all the different keyboard functions Make the most of your mouse Send email direct from Word